La recherche interdisciplinaire en santé: Retour sur l’expérience de l’Institut d’été en recherche interdisciplinaire en santé 2003 - O’Reilly, Louise (Can J Public Health, 2006)
Health care professionals are increasingly called upon to work collaboratively. This commentary discusses our experience at the Summer Institute on Interdisciplinary Health Research, which aimed to increase the capacity of future Canadian researchers to work with health professionals from other disciplines. We discuss, in particular, our small group experience–the challenges we faced, and how we were able to resolve the internal conflicts that occurred. We also discuss the conditions necessary to engage in interdisciplinary work and offer suggestions to improve future initiatives to build interdisciplinary research capacity.